Application of the Precede and Proceed Model in the Development of Community-Based Daily Emergency First Aid Management Training - Harnanto, Addi Mardi; Sunarto, Sunarto; Sumardino, Sumardino (JKG (JURNAL KEPERAWATAN GLOBAL), 2023)
ABSTRACTBackground: Emergency conditions that occur in society can occur at any time and anywhere. If this emergency condition is not handled properly, it will result in the threat of death and disability for society, which is certainly not in line with the SDGs ideals that have been proclaimed. It is necessary to increase the number of community members who have first aid competency so that it can reduce mortality and morbidity rates. In an effort to increase the number of first aid workers who are prepared to provide first aid, a health promotion model is needed in first aid in emergency cases. Methods: A mixed method of qualitative and quantitative research with research and development (R&D) research was applied to produce a training model for the community. Health promotion model was tested in phase two on 50 respondents who were randomly divided into intervention and control groups. Both group was evaluated with pre-post test. Results: Community-Based Daily Emergency First Aid Management Training gives a positive effects in knowledge, skills, and attitude of respondent with sig 0.00. Conclusion: The conclusion of this research is that the Community-Based Daily Emergency First Aid Management Training Model increases community competence in carrying out first aid for everyday emergency situations